A Possible Case of Vertical Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in a Newborn With Positive Placental In Situ Hybridization of SARS-CoV-2 RNA. (5th September 2020) - Alamar, Ihab; Abu-Arja, Mohammad H; Heyman, Taryn; Roberts, Drucilla J; Desai, Niyati; Narula, Pramod; Dygulska, Beata
Abstract: Little is known about the effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the coronavirus disease 2019 (COVID-19) on pregnant mothers and their infants. Moreover, there is no definitive evidence that SARS CoV- 2 can be vertically transmitted from an infected mother to the unborn fetus.